Analisis Integrasi Pasar Beras di Provinsi Bali - AGUNG, I DEWA GEDE; DARYANTO, JOKO (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 1 (2017), 2017)
Analysis of Rice Market Integration in The Province of Bali The creation of market integration in Indonesia will guarantee production stabilityand the national rice consumption. One of the criteria for integration of the marketcan be seen from the integration level among the rice markets. This study aimed tolook at the degree of integration of rice markets in Bali Province. The data used wasthe real price of rice in the local market as well as data from BPS from 2011 to 2015.To the market integration, it was measured based on IMC (Index of MarketConnection). The results showed that Bali rice market integration integrated in theshort terms with other provinces except with Central Java, South Sumatra, andLampung. In the long terms Bali integrated with other provinces, and best integratedwith West Java, Central Java, Yogyakarta, East Java, and NTB, with their respectiveelasticity transmissions of 0.75; 0.88; 0.82; and 0.79. The role of government isexpected to build good information network, so farmers as producers can have betterbaraining position in determining the prices at the producer level.
Keywords: market integration; rice; index of connection